A network analysis approach to functioning problems in first psychotic episodes and their relationship with duration of untreated illness: Findings from the PAFIP cohort. (April 2021) - Izquierdo, Ana; Cabello, María; de la Torre-Luque, Alejandro; Ayesa-Arriola, Rosa; Setien-Suero, Esther; Mayoral-van-Son, Jacqueline; Vazquez-Bourgon, Javier; Ayuso-Mateos, Jose Luis; Crespo-Facorro, Benedicto; ,
Abstract: Background: The domains of functioning affected by first episode of psychosis (FEP) could be analysed as forming a network of interacting or even reinforcing elements. The reasons why longer duration of untreated psychosis (DUP) might be related to higher disability are not still clear. The aim of the present study is to evaluate how different areas of functioning are inter-related according to the length of DUP in patients with FEP, with a particular focus on studying the relative influence of each other according to lengthy delays in initial treatment. Method: 441 participants in an epidemiological and intervention program of first episode psychosis (PAFIP) were included in our study. Functioning problems at baseline were assessed with the WHO Disability Assessment Schedule (DAS). Three networks of functioning domains have been estimated according to the length of DUP. Results: All the DAS items took part in the different networks. We have not found differences across the edge weights in the short, medium and long DUP groups. The domains "social withdrawal", "participation in the household activities", "general interest and information", and "low level of activity" seem to act as bridge items with other areas of functioning in people with longer DUP. Conclusions: Our results could have clinical implications for patients with longer DUP, in which case, social withdrawal, household activities, level of activity and general interest in the world around them, could be high-priority target areas of treatment, since they seem to be mediating the relation between others areas of functioning.